HUBUNGAN USIA DAN PARITAS IBU DENGAN KEJADIAN PREEKLAMPSIA BERAT DI RUMAH SAKIT UMUM DAERAH SEKAYU - Hera zahara Ayu saputri, (Jurnal Kesehatan Ilmiah Indonesia (Indonesian Health Scientific Journal), 2025)
According to WHO, the Maternal Mortality Rate (MMR) is that there are 810 women who die every day as a result of complications during pregnancy and childbirth. Preeclampsia is an increase in blood pressure at 20 weeks gestational age of 140/90 mmHg, accompanied by proteinuria of 300mg/24 hours or confirmed (+). Preeclampsia is a disease that arises with signs of hypertension, oedema, and urinary protein arising due to pregnancy and childbirth. To determine the relationship between maternal age and parity with the incidence of severe preeclampsia at Sekayu Regional General Hospital in 2024. This study uses the Survey Analytic method with a Cross Sectional approach. The population in this study is all pregnant women at the Sekayu Regional General Hospital in 2024 totaling 2,795 people. The sample of this study was taken from a part of the population, namely some pregnant women at the Sekayu Regional General Hospital in 2024 as many as 350 respondents. The sampling technique in this study is random sampling. The data taken is secondary data. Bivariately showed that there was a relationship between age and the incidence of severe preeclampsia p value = 0.001, there was a relationship between maternal parity and the incidence of severe preeclampsia p value = 0.001. These results conclude that the age and parity of pregnant women are related to the incidence of preeclampsia at the Sekayu Regional General Hospital in 2024 Keywords : Preeclampsia Severity, Age, Maternal Parity